Pengolahan Limbah Kulit Singkong Menjadi Tepung dengan Lama Waktu Perendaman CaCo3 dan Suhu Oven yang Berbeda - susanto, joko; , Dr. Siti Chalimah, M.Pd (2015)
WASTE PROCESSING INTO MEAL WITH SKIN SINGKONG IMMERSION CaCO3 TIME AND TEMPERATURE OVEN DIFFERENT Joko Susanto, A420 110 011, Department of Biology Education,The Faculty of Education, University of Muhammadiyah Surakarta, 2015, 83 pages. ABSTRACT Leather cassava is waste that still contain high nutrient and can be processed into flour. Skin contains HCN cassava which can be reduced by soaking, drying, boiling and fermentation. Lime water immersion can reduce sap or mucus, relieving distorted, making durable and prevent browning. The purpose of this study utilizing cassava peel in the manufacture of starch and know the content of protein, moisture content, as well as the organoleptic properties of the skin cassava flour. The treatment in this study was a long time soaking solution of CaCO3 1 hour, 2 hours, 3 hours and the temperature of the oven 300C, 400C, 500C with repetitions three times. Parameters measured include protein content, moisture content and organoleptic properties of the protein content of data analysis using the Kruskal-Wallis, while the water content and organoleptic test using a Two Way Anova. The results showed the highest protein content in the treatment of CaCO3 2 hours soaking time and oven temperature of 300C is 3.03 grams. Highest water levels at treatment 3 hours soaking time and oven temperature of 300C is 81.30%. The best color in the treatment of CaCO3 soaking time of 2 hours and 3 hours at a temperature of 500C oven. Organoleptic taste the soaking treatment CaC03 3 hours at a temperature of 300C oven, soaking CaCO3 1 hour at 400C oven temperature, soaking CaCO3 3 hours at a temperature of 400C oven produces discomfort, while other treatments are good taste. Organoleptic best texture on the old treatment of soaking CaCO3 3 hours at a temperature of 400C oven. The most excellent organoleptic properties in the treatment of soaking time of 2 hours and 3 hours at a temperature of 500C oven. Keywords: cassava flour skin, CaCO3 solution, soak time, the temperature of oven